Perkembangan Integrasi Digital Untuk Mendorong Digitalisasi Ekonomi di Kawasan Asean - Arief Maulana; Yana Suryana (Journal of Economics and Regional Science, 2024)
The digitalization of the economy is rapidly becoming the main driver capable of driving super-fast economic development. However, contrary to the ideal expectations, ASEAN still faces many challenges in promoting digital integration, one of which is the sizeable disparity among ASEAN countries in economic digitization. This actual condition (das sein) creates a gap with the main objective (das sollen). The main purpose of this article is to analyze the development of ASEAN's digitalization, explain the current picture of economic digitization, analyze the challenges in driving the digital economy and how to commit to it. The method used in this study is a literature study with a descriptive review variant. The study results show that taking advantage of the opportunities of an integrated digital economy will spur domestic economic growth. The use of technology and digital innovation also accelerates the productivity of the ASEAN region to be able to compete with other regions. The obstacles to digital economic integration that are still facing ASEAN are the low level of digital literacy and skills and the development of strategies that are not following the ASEAN Masterplan. Meanwhile, the key problems associated with digital integration commitments include wide digital gaps across ASEAN countries.